2005
DOI: 10.2325/jbcs.12.149
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Carcinosarcoma of the Breast

Abstract: Carcinosarcoma is a rare malignant tumor of the breast. A 59-year-old woman was admitted to our hospital with a complaint of a right breast mass for one month. The mass grew rapidly, and modified radical mastectomy was performed. Based on the histological findings of carcinomatous and sarcomatous components entangled without a transition area, and the results of immunohistochemical staining, carcinosarcoma of the breast was diagnosed. Within 9 months of the surgery, a recurrent lesion appeared in her chest wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 5 publications
2
41
0
1
Order By: Relevance
“…Patients should be considered for routine screening in terms of metastases. Lung metastases, brain, bone and liver metastases are more frequent and the prognosis of these patients is worse (6). Tumor size, high nuclear grade, triple negative disease, lymphovascular invasion and distant metastasis are poor prognostic factors (20,21,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients should be considered for routine screening in terms of metastases. Lung metastases, brain, bone and liver metastases are more frequent and the prognosis of these patients is worse (6). Tumor size, high nuclear grade, triple negative disease, lymphovascular invasion and distant metastasis are poor prognostic factors (20,21,24).…”
Section: Discussionmentioning
confidence: 99%
“…These tumors are thought to originate from malignant myofibroblasts or metaplastic differentiation of malignant epithelial cells within myofibroblasts (5). It has been reported that breast carcinosarcomas have a poor prognosis and a high risk of local-regional recurrence (6). These tumors usually do not express estrogene or progesterone receptors and HER-2/neu oncogene.…”
Section: Introductionmentioning
confidence: 99%
“…52 Human breast carcinosarcomas are also rare with an incidence estimated to 0.1 to 0.2% of breast carcinomas. 53 However, they are very aggressive with a poor prognosis. True carcinosarcoma is strictly defined as a mixed tumor with both epithelial and mesenchymal components without a transition zone between the two elements.…”
Section: Discussionmentioning
confidence: 99%
“…This tumor type has infrequent occurrence in dogs; it features rapid tumor growth and prolonged periods of post-surgical survival (Misdorp et al, 1999). They are rare tumors in women and have a poor prognosis compared to other carcinomas (Tokudome et al, 2005). In the dog, the clinical and pathological characteristics are similar to those described in humans (Cassali et al, 2011).…”
Section: Introductionmentioning
confidence: 59%